A JURIDICAL STUDY OF THE CHURCH AS A LEGAL SUBJECT IN INDONESIA - Yose Ferlianto (jfpublisher, 2025)
This study examines the status of the church as a legal subject and the regulation of its ownership rights as a religious institution in Indonesia. The research aims to analyze the legal framework governing the status of the church and evaluate the regulations related to its ownership rights. The methodology is a normative juridical and conceptual approach, with data collection through literature review and analysis of relevant legislation. The legal framework includes the constitution, statutory regulations, and Staatsblad 1927 No. 156, 157, and 532, which remain in effect pursuant to Article 1 of the Transitional Provisions of the 1945 Constitution. The study's findings indicate that churches in Indonesia are recognized as legal subjects, although not explicitly mentioned in the current legislation. Several legal provisions provide a legal basis for churches to own assets, but challenges remain in their implementation. This research contributes to understanding the legal status of churches and offers recommendations to improve the legal framework concerning church ownership rights, including broader legal protection and reconstruction of ownership regulations.